Precopulatory Sexual Cannibalism Causes Increase Egg Case Production, Hatching Success, and Female Attractiveness to Males. (1st March 2014) - Pruitt, Jonathan N.; Berning, Aric W.; Cusack, Brian; Shearer, Taylor A.; McGuirk, Mathew; Coleman, Anna; Eng, Robin Y. Y.; Armagost, Fawn; Sweeney, Kayla; Singh, Nishant; Koenig, W.
Abstract Precopulatory sexual cannibalism is an extreme form of sexual conflict that can entail significant costs to the cannibalized individual and a variety of costs and benefits to the cannibal itself. Characterizing these costs and benefits is fundamental to our understanding of how this behavior evolves. Using the spider Agelenopsis pennsylvanica, we tested the reproductive consequences of precopulatory sexual cannibalism by staging cannibalization events and comparing the performance of experimental cannibals against natural cannibals (i.e., those that cannibalized on their own) and non‐cannibals. We found two performance benefits associated with precopulatory sexual cannibalism: first, experimental cannibals were more likely to produce egg cases than non‐cannibals, and second, egg cases from experimental cannibals and natural cannibals were significantly more likely to hatch than those produced by non‐cannibals. We then tested whether males were more likely to approach the webs of experimental cannibals vs. non‐cannibalistic control females. Our data demonstrate that sexual cannibalism increases female attractiveness to males. Although this result seems counterintuitive, in fact, rates of precopulatory sexual cannibalism were much lower in females that had already cannibalized their first male: 38% of sexually naïve females engaged in precopulatory sexual cannibalism, whereas only 5% of females engaged in cannibalism a second time. Thus, males that approach cannibals receive two benefits: they are less likely to be cannibalized precopula, and they have the possibility of mating with females that have a higher probability of producing viable egg cases. Taken together, our data suggest that precopulatory sexual cannibalism affords females numerous benefits and may have a hand in shaping male mate choice decisions.